Factors affecting flower initiation and development in Dutch iris - Elphinstone, E.D. (1986)
Flower initiation and development to anthesis in Dutch iris were investigated using three cultivars, 'Wedgwood', 'Ideal' and 'Professor Blaauw'. In particular, environmental effects on flower initiation and on flower abortion were studied.